Improving Reading Comprehension by Using Contextual Teaching and Learning (CTL) at Secondary School in Jember - Ernawati, Eka; Ghozali, Imam; Nur Tjendani, Endah (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2022)
The purpose of this research is to know how using contextual teaching and learning (CTL) method can improve the eighth-grade students’ reading comprehension at SMP Negeri 2 Mayang Jember. The design of the research is Classroom Action Research: which uses test as the instrument of the research. The research subject is the eighth-grade students is 38 students. The result of reading test data in cycle 1 showed that 12 from 38 students, who have scored ≥ 70 were 31,57%. It means the result did not achieve the target. The researcher needs to revise the plan or technique in cycle 2. All activities done with the partner both defining difficult word and discussion. in cycle 2 there were 30 from 38 of the students who scored ≥ 70 were 78,94%. It means the target score in reading test achieved the target score. The action was stopped because requirement 75% students reading test could achieve the target score. It can be concluded by using contextual teaching and learning (CTL) method could improve the students’ reading comprehension at SMP Negeri 2 Mayang